Low-methoxyl pectin-zeolite hydrogels controlling drug release promote in vitro wound healing - BATIREL, SAİME (WILEY, 2019)
This study presents the design of novel hydrogel films, based on low-methoxyl (LM) pectin and NaA- or ZnA-zeolite particles, to serve as wound dressing materials with controlled drug delivery properties. We studied the effects of the preparation method of hydrogels, the amounts of crosslinker, drug and zeolite, and the type of cation in zeolites on the drug release mechanisms from the hydrogels. Ionic strengths of both film and external medium dictated the drug release behavior of the films, while the other parameters also played essential roles. NaA-zeolite hydrogels prepared using membrane diffusion controlled system, could reach a drug release ratio of 86% within 5 h. The drug-free hydrogels displayed no cytotoxicity while supporting cell proliferation and migration. Our cost-effective LM pectin-zeolite hydrogels promise to be effective wound dressing materials with controlled drug delivery ability, transparency, good swelling properties, ability to hold fluids, good oxygen transmission rate, and biocompatibility. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47640.
Keywords: biomedical applications; biopolymers and renewable polymers; drug delivery systems; DELIVERY; COMPOSITE; SCAFFOLDS; SILVER; FILMS; ZINC; ANTIBACTERIAL; PERMEABILITY; MANAGEMENT; MICROWAVE